Symptomatic pleomorphic adenoma of the submandibular gland in a malepatient: A case report and review of the literature (Indian Journal of Case Reports, 2024)
Salivary gland tumors represent only 1–4% of head-and-neck tumors, with submandibular gland tumors representing around 10% of salivary gland tumors. Although rarely seen, submandibular pleomorphic adenoma is the most common of the submandibular gland neoplasms (36%). These tumors have a female predominance and present as a painless mass. We report a 42-year-old male patient with a 6-month history of swelling in his left submandibular region due to submandibular pleomorphic adenoma in a hospital in North India. Many diseases in the submandibular region with overlapping clinical pictures make diagnosing difficult. Integrated clinical, radiological, and cytological approaches help in differential diagnosis and making a provisional diagnosis. However, the final diagnosis can be established only by histopathology.